Tethered balloon operation for wintering aerosol measurements in the lower troposphere at Syowa Station, Antarctica - Keiichiro Hara; Kazuo Osada; Takashi Yamanouchi (Antarctic Record, 2007)
The 46th Japanese Antarctic Research Expedition (JARE-46) carried out twenty seven tethered-balloon-borne aerosol measurements at Syowa Station for better understanding of aerosol chemical and physical properties in the lower troposphere from 6th January 2005 until 11 December 2005. This report summarizes the plan, preparation, field activities and some troubles/problems in the tethered-balloon observations.